Steel bridge deck slab bridge deck pavement structure based on fly ash geopolymer concrete and pavement method thereof

By using a combined structure of fly ash ground polymer concrete layer and epoxy resin adhesive bonding layer on the steel bridge deck, the fatigue and durability problems in the existing steel bridge deck construction technology are solved, and efficient and environmentally friendly Bridge deck paving effect.

CN119392603APending Publication Date: 2025-02-07SHANDONG LUQIAO GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411424581.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The construction technology of existing steel bridge decks has problems such as fatigue problems, insufficient durability of the pavement layer, fatigue cracks in welding details, and difficulty in installing prefabricated concrete bridge decks, and the environmental burden and rut resistance of ordinary concrete are insufficient.

Method used

The steel bridge deck paving structure based on fly ash ground polymer concrete is adopted, including steel bridge deck panels, bonding layers, fly ash ground polymer concrete layer and asphalt pavement layer, and is composed of epoxy resin adhesive and quartz sand. The bonding layer connects the steel bridge deck with the fly ash ground polymer concrete layer to improve the integrity and durability of the structure.

Benefits of technology

It improves the integrity and durability of the steel bridge deck, enhances the fatigue resistance of the structure, reduces its own weight, and significantly reduces CO2 emissions and production energy consumption, and improves construction efficiency and bridge deck service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392603A_ABST
    Figure CN119392603A_ABST
Patent Text Reader

Abstract

The invention relates to the field of steel bridge deck pavement, in particular to a steel bridge deck slab bridge deck pavement structure based on fly ash geopolymer concrete and a pavement method thereof. The surface pavement structure sequentially comprises a steel bridge deck, a bonding layer, a fly ash geopolymer concrete layer and an asphalt pavement layer from bottom to top; the bonding layer is composed of an epoxy resin adhesive and quartz sand embedded in the epoxy resin adhesive; the fly ash geopolymer concrete layer is a fly ash geopolymer concrete plate made of fly ash geopolymer concrete. The steel bridge deck and the coal ash geopolymer concrete are connected into a whole through the epoxy resin adhesive instead of adopting a shear nail in the prior art, the connection between the geopolymer concrete layer and the steel bridge deck layer is enlarged, the contact area between the geopolymer concrete layer and the steel bridge deck layer is enlarged, and the integrity of the structure is further improved. And specifically, the stress amplitude at fatigue details is reduced through cooperative stress, fatigue crack propagation is avoided, and the service life is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of steel bridge deck pavement, and in particular to a steel bridge deck pavement structure based on fly ash geopolymer concrete and a paving method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] The stress and deformation characteristics of steel bridge decks are far more complex than those of highway pavements, which makes the strength, deformation capacity, temperature characteristics and fatigue durability of the bonding layer and the pavement layer more stringent. At present, the steel bridge deck structure mainly connects the concrete layer and the steel bridge deck into a whole by welding shear nails. However, engineering practice shows that connecting the two by welding studs will cause fatigue problems in orthotropic steel bridge decks and damage to the pavement layer, which will significantly reduce the service life and safety of the structure. In addition, the fatigue crack problem at the welding details of orthotropic steel bridge decks will seriously restrict the size of local stiffness. At the same time, the pavement layer is subjected to local high stress under the influence of vehicle load, overload, environment and other factors, and is prone to cracking, rutting, delamination and other diseases. While improving the local stiffness of the structure, the self-weight of the structure must also be considered. Therefore, the existing design method of orthotropic steel bridge decks is not enough to solve its fatigue and pavement durability problems.

[0004] In addition to the above problems, clustered group nail connectors often cause problems in the installation of precast concrete bridge decks during actual construction because the position of the welds or steel bars deviates from the designed position. This situation will cause conflicts between the positions of the welds and steel bars, making the installation of the bridge deck difficult. In order to solve this problem, it is often necessary to cut the welds or steel bars on site, which not only prolongs the construction period, but also greatly reduces the connection efficiency and leaves safety hazards. In addition, reserving group nail holes on the precast concrete bridge deck will greatly weaken the effective cross-section of the concrete. Especially when prestressing, stress concentration is prone to occur at the corners, resulting in uneven stress distribution on the cross section, leaving cracking hazards, thereby reducing the durability of the structure. Therefore, the field of steel bridge deck paving urgently needs to develop a new type of bridge deck paving structure to improve the existing steel bridge deck construction technology.

[0005] In addition, in the field of building materials, ordinary concrete is the dominant material, and its global annual production has remained stable at more than 5 billion tons. This huge production scale not only intensifies the consumption of natural resources such as sand and stone, but also brings with it a significant environmental burden in the cement production process, especially the large amount of CO2 released by cement manufacturing, which has become a key factor in aggravating the greenhouse effect. In addition, the bending and flexural resistance of ordinary concrete commonly used in bridge deck pavement is gradually insufficient to meet the anti-rutting capacity brought by the current traffic volume. Summary of the invention

[0006] In order to overcome the above problems, the present invention provides a steel bridge deck pavement structure based on fly ash geopolymer concrete and a paving method thereof.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:

[0008] The first aspect of the present invention provides a steel bridge deck pavement structure based on fly ash geopolymer concrete, which comprises, from bottom to top, a steel bridge deck, a bonding layer, a fly ash geopolymer concrete layer and an asphalt pavement layer;

[0009] The bonding layer is composed of epoxy resin adhesive and quartz sand embedded in the epoxy resin adhesive;

[0010] The fly ash geopolymer concrete layer is a fly ash geopolymer concrete slab made of fly ash geopolymer concrete.

[0011] In one or more embodiments, the thickness ratio of the steel bridge deck, the bonding layer, the fly ash geopolymer concrete layer and the asphalt pavement layer is 1:0.2-0.4:1.7-2.8:1.2-2.1.

[0012] In one or more embodiments, an anti-rust layer is provided between the steel bridge deck and the bonding layer.

[0013] Preferably, the thickness of the anti-rust layer is 60-80 μm.

[0014] In one or more embodiments, in the bonding layer, the particle size of the quartz sand is 3 to 6 mm.

[0015] In one or more embodiments, the spreading amount of quartz sand in the bonding layer is 4 to 9 kg / m 2 .

[0016] Embedding quartz sand with a particle size in the epoxy resin adhesive can increase the friction coefficient of the bonding section and ensure the combined effect of the bonding layer.

[0017] In one or more embodiments, transverse steel bars and longitudinal steel bars are evenly embedded in the fly ash geopolymer concrete slab, and binding steel wires are installed at the intersections of the transverse steel bars and the longitudinal steel bars.

[0018] Preferably, the transverse steel bars and the longitudinal steel bars are hot-rolled ribbed steel bars with the same diameter, both of which are 11 to 13 mm, preferably 12 mm.

[0019] In one or more embodiments, the fly ash geopolymer concrete slab is rectangular in shape and has an area of ​​3 to 5 m 2 , preferably 4m 2 .

[0020] In one or more embodiments, cast-in-place strips are provided between adjacent fly ash geopolymer concrete slabs in the transverse and longitudinal directions, and steel bars are embedded in the cast-in-place strips along the length direction of the cast-in-place strips.

[0021] Preferably, the width of the cast-in-place strip is 200-300 mm, preferably 240 mm.

[0022] Preferably, the fly ash geopolymer concrete slabs adjacent in transverse direction are connected by transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs; and the fly ash geopolymer concrete slabs adjacent in longitudinal direction are connected by longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs.

[0023] Further preferably, the transverse reinforcements or longitudinal reinforcements of adjacent transverse or longitudinal fly ash geopolymer concrete slabs are connected by welding.

[0024] Further preferably, tying steel wires are installed at the intersections of the transverse steel bars or the longitudinal steel bars in the fly ash geopolymer concrete slab and the steel bars buried in the cast-in-place zone.

[0025] In one or more embodiments, the raw materials of the fly ash geopolymer concrete layer include: cement, slag, fly ash, water, water glass and alkali activating liquid.

[0026] Preferably, the cement comprises Portland cement.

[0027] Preferably, the fly ash is low-calcium fly ash from a power plant; the fineness of the fly ash is 0.09-0.12 mm.

[0028] Preferably, the modulus of water glass is 1.8.

[0029] Preferably, the alkaline activating solution is NaOH solution.

[0030] Preferably, the method for preparing fly ash geopolymer concrete comprises the following steps:

[0031] After cement and fly ash are mixed evenly according to the proportion, slag is added and mixed evenly to obtain a first mixture;

[0032] Water, alkali activating liquid and water glass are sequentially added to the first mixture, and the mixture is evenly mixed to obtain fly ash geopolymer concrete.

[0033] The second aspect of the present invention provides a paving method for the above-mentioned steel bridge deck pavement structure based on fly ash geopolymer concrete, comprising the following steps:

[0034] (1) Apply a layer of anti-rust layer on the upper surface of the treated steel bridge deck, wait for the anti-corrosion layer to dry after evenly applying it, and then apply epoxy resin adhesive evenly again. After applying for 1.5 to 2.5 hours, evenly spread quartz sand; apply pressure on the surface of quartz sand to embed the quartz sand into the epoxy resin adhesive;

[0035] (2) laying the prefabricated fly ash geopolymer concrete slab on the upper surface of the bonding layer, and connecting the prefabricated fly ash geopolymer concrete slabs adjacent in the transverse and longitudinal directions on site;

[0036] (3) Laying asphalt pavement on the upper surface of the prefabricated fly ash geopolymer concrete slab.

[0037] In one or more embodiments, an anti-rust layer is applied to the steel bridge deck before the epoxy resin adhesive is applied.

[0038] In one or more embodiments, in step (1), the epoxy resin adhesive is in an uncured state 1.5 to 2.5 hours after coating.

[0039] In one or more embodiments, in step (2), the method of connecting the prefabricated fly ash geopolymer concrete panels adjacent to each other in the transverse direction and in the longitudinal direction on site comprises:

[0040] S1. At the cast-in-place zone, the fly ash geopolymer concrete slabs adjacent in the transverse direction are welded through the transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs; and the transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs are tied to the longitudinal steel bars in the cast-in-place zone with steel wires;

[0041] At the cast-in-place strip, the longitudinally adjacent fly ash geopolymer concrete slabs are welded through the longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs; and the longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs are tied to the transverse steel bars in the cast-in-place strip with steel wires;

[0042] S2. Use concrete to cast the cast-in-place strip.

[0043] In one or more embodiments, in S2, the concrete is C50 concrete.

[0044] The beneficial effects of the present invention are:

[0045] (1) The steel bridge deck and fly ash geopolymer concrete are connected as a whole using epoxy resin adhesive instead of shear nails, which increases the connection between the geopolymer concrete layer and the steel bridge deck, expands the contact area between the two, and further improves the integrity of the structure. Specifically, it can be shown in coordinated force, reduce the stress amplitude at fatigue details, avoid fatigue crack propagation, and prolong the service life.

[0046] The fly ash geopolymer concrete of the present invention has higher mechanical properties than ordinary concrete and alkali-activated ultra-high performance concrete, and its 7d flexural strength can reach 37MPa, and its 28d flexural strength can reach 39MPa. The 7d compressive strength of the fly ash geopolymer concrete can reach 112MPa, and the 28d compressive strength can reach 140Mpa, which fully meets the needs of steel-concrete composite structure bridge deck pavement concrete. At the same time, the fly ash geopolymer concrete also shows significant environmental advantages, and its CO2 emission is only about one-fifth of that in the cement production process, and almost no toxic gas emissions are generated. At the same time, its production energy consumption is only one-fourth of that of cement.

[0047] (3) The fly ash geopolymer concrete-based steel bridge deck provided by the present invention reduces the overall deadweight of the bridge deck, increases the fatigue resistance of the bridge deck, and improves the service life of the steel bridge deck.

[0048] (3) Compared with traditional bridge deck paving, the present invention adopts the method of paving fly ash geopolymer concrete slabs in blocks, which can improve the overall construction speed and reduce the difficulty of construction. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0050] Figure 1 It is a steel bridge deck pavement structure based on fly ash geopolymer concrete;

[0051] Figure 2 A schematic diagram of the structure for installing the concrete slab onto the bridge deck by staggered paving;

[0052] Figure 3 A structure for prefabricated fly ash geopolymer concrete slabs and a structure for providing current strips between adjacent fly ash geopolymer concrete slabs;

[0053] Figure 4 is the load-slip curve. DETAILED DESCRIPTION

[0054] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0055] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0056] The epoxy resin adhesive used in the following embodiments is Swiss Sika 30 epoxy resin adhesive.

[0057] Example 1

[0058] Preparation of fly ash geopolymer concrete:

[0059] The length, width and height are 2000mm×2000mm×40mm, and the area is 4m 2 Take the fly ash geopolymer concrete as an example, which is composed of the following materials in the following mass proportions:

[0060] 100kg cement, 30kg fly ash, 25kg water glass, 10kg NaOH solution with a pH value of 11.7±0.1, 28kg slag, and 16kg water.

[0061] The preparation method is as follows:

[0062] The cement and fly ash are fully mixed and stirred for 20 minutes using a mixer, and then slag is added during the continuous stirring process, and fully stirred for 10 minutes to obtain a first mixture;

[0063] After adding water to the first mixture, the mixture was stirred again with a stirrer for 20 minutes, and after 20 minutes, the alkaline excitation solution was added thereto, and the mixture was stirred again for 5 minutes to obtain a second mixture;

[0064] The water glass added to the second mixture is fully mixed and stirred in a mixer for 10 minutes to obtain a fly ash geopolymer concrete material;

[0065] The fly ash geopolymer concrete material is introduced into the test mold for molding and curing.

[0066] Example 2

[0067] Preparation of fly ash geopolymer concrete:

[0068] The length, width and height are 2000mm×2000mm×40mm, and the area is 4m 2 Take the fly ash geopolymer concrete as an example, which is composed of the following materials in the following mass proportions:

[0069] 110kg cement, 32kg fly ash, 25kg water glass, 8kg NaOH solution with a pH value of 11.7±0.1, 29kg slag, and 29kg water.

[0070] The preparation method is the same as that of Example 1.

[0071] Example 3

[0072] Preparation of fly ash geopolymer concrete:

[0073] The length, width and height are 2000mm×2000mm×40mm, and the area is 4m 3 Take the fly ash geopolymer concrete as an example, which is composed of the following materials in the following mass proportions:

[0074] 90kg cement, 26kg fly ash, 20kg water glass, 10kg NaOH solution with a pH value of 11.7±0.1, 20kg slag, and 25kg water.

[0075] The preparation method is the same as that of Example 1.

[0076] Comparative Example 1

[0077] This comparative example uses ordinary concrete to prepare concrete, and the specific preparation method is:

[0078] 78kg cement, 30kg coarse aggregate, 70kg river sand, 23kg water. The cement is ordinary Portland cement with a strength grade of 42.5, the particle size of the river sand is 0.5-1.0mm, and the coarse aggregate is crushed stone with a size of 5-20mm.

[0079] The preparation method is:

[0080] (1) According to the mix ratio of ordinary concrete, weigh the cement, river sand, coarse aggregate and water according to the mass;

[0081] (2) Pour the prepared cement, river sand and coarse aggregate into a mixer and mix for 2 minutes to obtain a mixture;

[0082] (3) Pour two-thirds of the water into the mixture for wet mixing. After stirring for 2 minutes, pour the remaining water into the mixture and continue stirring to obtain ordinary silicate concrete.

[0083] Comparative Example 2

[0084] This comparative example is prepared using steel fiber concrete, and the specific preparation method is as follows:

[0085] 100kg cement, 80kg silica fume, 60kg river sand, 20kg water, 5kg water reducer; the cement is ordinary Portland cement with a strength grade of 42.5; the particle distribution range of silica fume is 0.09-0.13μm, the maximum particle size of river sand is less than 1mm, the steel fiber is copper-plated steel fiber, 10mm long and 0.12mm in diameter; the model of the water reducer is Sika water reducer.

[0086] The preparation method is:

[0087] (1) According to the mix ratio of steel fiber concrete, cement, river sand, silica fume, water and steel fiber are weighed according to mass;

[0088] (2) Pour the prepared cement, river sand, silica fume, steel fiber, and water reducing agent into a mixer and mix for 2 minutes to obtain a mixture.

[0089] (3) Pour two-thirds of water into the mixture for wet mixing. After stirring for 2 minutes, pour the remaining water into the mixture and continue stirring to obtain steel fiber concrete.

[0090] After the mixing of the fly ash geopolymer concrete of bridge powder of Examples 1 to 3 of the present invention and the concrete of Comparative Examples 1 to 2 was completed, the slump expansion was tested, and the slurry was poured into a standard mold for molding. After standing for 1 day, the mold was removed, and then, it was placed in a standard curing room for standard curing to a specified age, and the mechanical properties and durability performance tests were carried out. The test standards and results are shown in Table 1.

[0091] The crack resistance performance was determined by making standard test blocks according to the standard GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" and recording the number of cracks in the concrete after curing for 28 days, thereby obtaining the number of cracks per unit area of ​​fly ash geopolymer concrete.

[0092] The compressive strength and flexural strength are determined by referring to the standard GB / T50081~2019 "Standard Test Methods for Physical and Mechanical Properties of Concrete" to make standard test blocks and test their 7d and 28d flexural strength and bending strength.

[0093] The shrinkage performance is based on the standard test blocks made in accordance with GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", and the 28d shrinkage rate data is recorded in accordance with GB / T50082-2009 "Standard for Test Methods for Long-term Properties and Durability of Ordinary Concrete".

[0094] Table 1 Concrete performance test results of Examples 1 to 3 bridge flour fly ash geopolymer concrete and Comparative Examples 1 to 2

[0095]

[0096]

[0097] From the above results, it can be seen that the fly ash geopolymer concrete prepared according to the present invention has higher mechanical properties than ordinary concrete and alkali-activated concrete. Its 7d flexural strength can reach 37MPa, and its 28d flexural strength can reach 39MPa. The 7d compressive strength of the fly ash geopolymer concrete can reach 112MPa, and the 28d compressive strength can reach 140Mpa, which fully meets the needs of steel-concrete composite structure bridge deck pavement concrete.

[0098] Example 4

[0099] Figure 1 For the steel bridge deck pavement structure based on fly ash geopolymer concrete, reference Figure 1 , this embodiment provides a steel bridge deck pavement structure based on fly ash geopolymer concrete, which includes, from bottom to top, a steel bridge deck 1, an anti-rust layer 2, a bonding layer 3, a fly ash geopolymer concrete layer 4 and an asphalt pavement layer 5;

[0100] Wherein, the bonding layer 2 is composed of epoxy resin adhesive and quartz sand embedded in the epoxy resin adhesive;

[0101] The fly ash geopolymer concrete layer 3 is a fly ash geopolymer concrete slab made of fly ash geopolymer concrete.

[0102] The anti-rust layer 2 is an epoxy resin zinc-rich primer.

[0103] In this embodiment, the thickness ratio of the steel bridge deck 1, the anti-rust layer 2, the bonding layer 3, the fly ash geopolymer concrete layer 4 and the asphalt pavement layer 5 is 1:0.2:0.4:2:1.6.

[0104] Example 5

[0105] This embodiment provides a paving method for the steel bridge deck pavement structure based on fly ash geopolymer concrete in Embodiment 4, comprising the following steps:

[0106] (1) The upper surface of the steel bridge deck is shot blasted with a shot blasting machine to remove dust and rust on the upper surface of the steel bridge deck.

[0107] (2) Apply an anti-rust layer on the upper surface of the treated steel bridge deck. The anti-rust layer uses Langfang Xingfeng's epoxy resin zinc-rich primer. After the anti-corrosion layer is evenly applied and waits for the surface of the anti-corrosion layer to dry, apply the epoxy resin adhesive evenly again. After 2 hours of application, spread quartz sand evenly on the upper surface of the epoxy resin adhesive. The particle size of the quartz sand is 3 to 6 mm, and the spreading amount of silica sand is 4 to 9 kg / m 2, apply 100-150N pressure on the surface of quartz sand to embed part of the volume of quartz sand into the uncured epoxy resin adhesive.

[0108] (3) laying the prefabricated fly ash geopolymer concrete slab on the upper surface of the bonding layer, and connecting the prefabricated fly ash geopolymer concrete slabs adjacent in the transverse and longitudinal directions on site;

[0109] Specifically include: preparing prefabricated fly ash geopolymer concrete slabs; Figure 2 as well as Figure 3 , transverse and longitudinal steel bars are evenly buried in the fly ash geopolymer concrete slab, and tying wires are installed at the intersection of the transverse and longitudinal steel bars. The thickness of the transverse and longitudinal steel bars are hot-rolled ribbed steel bars, with a steel bar diameter of 12mm and a length of 200mm. The shape of the prefabricated fly ash geopolymer concrete slab is rectangular, with a length, width and height of 2000mm×2000mm×40mm, and an area of ​​4m 2 .

[0110] The prefabricated fly ash geopolymer concrete slabs were transported to the construction site and hoisted to the steel bridge deck. Figure 3 Since staggered paving can enhance the integrity of the bridge deck and make the prefabricated bridge decks fit closely and not loose, the concrete slabs are installed on the bridge deck by staggered paving.

[0111] In the process of staggered paving, refer to Figure 2 and Figure 3 , a longitudinal cast-in-place strip is provided between the fly ash geopolymer concrete slabs adjacent in the transverse direction, and longitudinal steel bars are embedded in the longitudinal cast-in-place strip. A transverse cast-in-place strip is provided between the fly ash geopolymer concrete slabs adjacent in the transverse direction, and transverse steel bars are embedded in the transverse cast-in-place strip. At the longitudinal cast-in-place strip, the fly ash geopolymer concrete slabs adjacent in the transverse direction are welded through the transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs; and the transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs are tied with the longitudinal steel bars in the cast-in-place strip by steel wire; At the transverse cast-in-place strip, the fly ash geopolymer concrete slabs adjacent in the transverse direction are welded through the longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs; and the longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs are tied with the transverse steel bars in the cast-in-place strip by steel wire. The size of the longitudinal and transverse cast-in-place strips is 2000×240mm. The internal steel bars are hot-rolled ribbed steel bars with a diameter of 12mm. C50 concrete is used to cast the longitudinal and transverse cast-in-place strips.

[0112] Example 6

[0113] A rigid paved bridge deck specimen was prepared using the fly ash geopolymer concrete prepared in Example 1 of the present invention, and its specific mechanical properties were tested.

[0114] The rigid paved bridge deck specimens are from bottom to top: steel plate (thickness 20mm, length 300mm, width 2300mm), anti-rust layer (thickness 0.07mm), epoxy resin adhesive layer (thickness 6mm) and fly ash geopolymer concrete slab without steel bars (thickness 40mm).

[0115] The preparation method comprises:

[0116] (1) The upper surface of the steel bridge deck is shot blasted with a shot blasting machine to remove dust and rust on the upper surface of the steel bridge deck.

[0117] (2) Apply a layer of anti-rust layer on the upper surface of the treated steel bridge deck. The thickness of the anti-rust layer is 0.07 mm. The anti-rust layer uses Langfang Xingfeng's epoxy resin zinc-rich primer. After applying it evenly, wait for the anti-corrosion layer to dry on the surface, and then apply 6 mm epoxy resin adhesive evenly again. The thickness of the epoxy resin adhesive is about 6 mm. Within 1 to 2 hours of application, evenly spread quartz sand on the upper surface of the epoxy resin adhesive. The particle size of the quartz sand is 3 to 6 mm, and the spreading amount of silica sand is 5 kg / m 2 , a pressure of 150N was applied to the surface of the quartz sand so that part of the volume of the quartz sand was embedded in the uncured epoxy resin adhesive.

[0118] (3) The prefabricated fly ash geopolymer concrete slab of Example 1 is laid on the upper surface of the bonding layer.

[0119] The static load test type is carried out using a reaction frame steel beam and a jack. The two ends of the test beam are respectively placed on the steel rig, with the upper end of the steel round bar hinged (non-sliding steel round bar) and one end simply supported (sliding steel round bar) to simulate the support constraint. The loading jack is loaded from top to bottom within the mid-span range, and the load is measured by the pressure sensor set between the jack and the reaction frame. In order to simulate the mechanical behavior of the composite bridge deck under the wheel load, the loading area is 200mm×300mm in the mid-span.

[0120] The test beam results can be expressed using load-slip curves ( Figure 4 ) indicates that when the load is before 110kN, there is no relative slip between the steel plate and the fly ash geopolymer concrete. When the load is loaded to 112kN to 140kN, the structure makes a violent sound and the deformation increases significantly, indicating that the bonding layer begins to enter the failure stage, the steel-concrete interface of the specimen begins to slip and dislocate, and obvious cracks begin to appear in the fly ash geopolymer concrete. When the load is loaded to 160kN, the external load on the test beam reaches the maximum value, the deformation is too large, and the loading is stopped.

[0121] Before the load reaches 112kN, the connection effect of the steel-concrete composite beam is good, the relative slip is almost 0, and the two coordinate with each other and have good joint force performance. As the load continues to increase, when the load reaches 112kN, the steel plate enters the material strengthening stage, and cracks begin to appear in the concrete. The relative slip between the two increases with the increase of the load. When the load reaches 160kN, the deformation increases sharply and the epoxy glue enters the destruction stage. The test results show that compared with ordinary bridge deck paving concrete, it has a stable combination effect before and after the steel cover plate yields, which meets the force requirements of orthotropic steel bridge decks.

[0122] The design method of ultra-high performance fly ash geopolymer concrete composite layer based on bonding layer can increase the bearing capacity of the specimen by 1.64 times, verifying the effectiveness of the design method proposed in the present invention.

[0123] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A steel bridge deck pavement structure based on fly ash geopolymer concrete, characterized in that: From bottom to top, it includes steel bridge deck, bonding layer, fly ash geopolymer concrete layer and asphalt pavement layer; The bonding layer is composed of epoxy resin adhesive and quartz sand embedded in the epoxy resin adhesive; The fly ash geopolymer concrete layer is a fly ash geopolymer concrete slab made of fly ash geopolymer concrete.

2. The steel bridge deck pavement structure based on fly ash geopolymer concrete according to claim 1, characterized in that: The thickness ratio of the steel bridge deck, the bonding layer, the fly ash geopolymer concrete layer and the asphalt pavement layer is 1:0.2-0.4:1.7-2.8:1.2-2.

1.

3. The steel bridge deck pavement structure based on fly ash geopolymer concrete according to claim 1, characterized in that: An anti-rust layer is provided between the steel bridge deck and the bonding layer; preferably, the thickness of the anti-rust layer is 60 to 80 μm; Or, in the bonding layer, the particle size of the quartz sand is 3 to 6 mm; Or, in the bonding layer, the spreading amount of quartz sand is 4-9 kg / m 2 .

4. The steel bridge deck pavement structure based on fly ash geopolymer concrete according to claim 1, characterized in that: Transverse steel bars and longitudinal steel bars are evenly embedded in the fly ash geopolymer concrete slab, and binding steel wires are installed at the intersections of the transverse steel bars and longitudinal steel bars; preferably, the transverse steel bars and longitudinal steel bars are hot-rolled ribbed steel bars with the same diameter, both of which are 11 to 13 mm, preferably 12 mm; Or, the fly ash geopolymer concrete slab is rectangular in shape and has an area of ​​3 to 5 m 2 , preferably 4m 2 .

5. The steel bridge deck pavement structure based on fly ash geopolymer concrete according to claim 1, characterized in that: Cast-in-place strips are provided between adjacent fly ash geopolymer concrete slabs in the transverse and longitudinal directions, and steel bars are embedded in the cast-in-place strips along the length direction of the cast-in-place strips; Preferably, the width of the cast-in-place strip is 200-300 mm, preferably 240 mm; Preferably, the fly ash geopolymer concrete slabs adjacent in the transverse direction are connected by transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs; the fly ash geopolymer concrete slabs adjacent in the longitudinal direction are connected by longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs; Further preferably, the method of connecting the transverse reinforcements or longitudinal reinforcements of adjacent transverse or longitudinal fly ash geopolymer concrete slabs is welding; Further preferably, tying steel wires are installed at the intersections of the transverse steel bars or the longitudinal steel bars in the fly ash geopolymer concrete slab and the steel bars buried in the cast-in-place zone.

6. The steel bridge deck pavement structure based on fly ash geopolymer concrete according to claim 1, characterized in that: The raw materials of the fly ash geopolymer concrete layer include: cement, slag, fly ash, water, water glass and alkali activating liquid; Preferably, the cement comprises Portland cement; Preferably, the fly ash is low-calcium fly ash from a power plant; the fly ash fineness is 0.09-0.12 mm; Preferably, the modulus of water glass is 1.8; Preferably, the alkaline activating solution is NaOH solution.

7. The steel bridge deck pavement structure based on fly ash geopolymer concrete according to claim 6, characterized in that: The preparation method of fly ash geopolymer concrete comprises the following steps: After cement and fly ash are mixed evenly according to the proportion, slag is added and mixed evenly to obtain a first mixture; Water, alkali activating liquid and water glass are sequentially added to the first mixture, and the mixture is evenly mixed to obtain fly ash geopolymer concrete.

8. The paving method of the steel bridge deck pavement structure of fly ash geopolymer concrete according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) The upper surface of the steel bridge deck is evenly coated with epoxy resin adhesive, and quartz sand is evenly spread 1.5 to 2.5 hours after the coating; pressure is applied on the surface of the quartz sand to embed the quartz sand into the epoxy resin adhesive; (2) laying the prefabricated fly ash geopolymer concrete slab on the upper surface of the bonding layer, and connecting the prefabricated fly ash geopolymer concrete slabs adjacent in the transverse and longitudinal directions on site; (3) Laying asphalt pavement on the upper surface of the prefabricated fly ash geopolymer concrete slab.

9. The paving method according to claim 8, characterized in that: Before applying epoxy adhesive to steel bridge decks, apply an anti-rust layer; Alternatively, in step (1), the epoxy resin adhesive is in an uncured state 1.5 to 2.5 hours after coating.

10. The paving method according to claim 8, characterized in that: In step (2), the method of connecting the prefabricated fly ash geopolymer concrete slabs adjacent to each other in the transverse direction and in the longitudinal direction on site comprises: S1. At the cast-in-place zone, the fly ash geopolymer concrete slabs adjacent in the transverse direction are welded through the transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs; and the transverse steel bars embedded in the adjacent fly ash geopolymer concrete slabs are tied to the longitudinal steel bars in the cast-in-place zone with steel wires; At the cast-in-place zone, longitudinally adjacent fly ash geopolymer concrete slabs are welded through longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs; and the longitudinal steel bars embedded in the adjacent fly ash geopolymer concrete slabs are tied to the transverse steel bars in the cast-in-place zone with steel wires.